The relationship between Libyan EFL learners' self-efficacy beliefs and their use of vocabulary learning strategies - Abozaid, Laila Aiyad Ali; Jalaluddin, Ilyana (Human Resource Management Academic Research Society, 2019)
The recent research investigated the relationship between Libyan English as a Foreign Language (EFL) learners’ beliefs and their use of Vocabulary Learning Strategies (VLSs). The respondents were 200 students studying English at Tripoli University, Faculty of Education-Janzour. The data was collected through two sets of instruments: (i) a questionnaire of vocabulary learning strategies which was designed by Schmitt (1997) to determine the frequency of VLS use and (ii) a questionnaire of Vocabulary Learning Self-Efficacy Beliefs adapted from a study conducted by Tseng (2006). Collected data was quantitatively analyzed utilizing the Statistical Package for the Social Sciences version 25. The results demonstrated that respondents of this study were medium-level users of strategy with average rating of 3.4 and standard deviation of 0.5 for overall rating use of strategy. Furthermore, the most used VLS category was determination strategies (3.74), while the category of metacognitive strategies (M= 3.16) was the least used among all the five VLSs used by the participants. Based on the results, learners had positive beliefs about vocabulary learning, which were significantly positively related to their use of vocabulary learning strategies (r= 0.511), in generally, and the use of five subcategories, in particularly. Thus, it was found that vocabulary learning strategies use increases as the self-efficacy of students increases.